Mediterranean quarantines, 1750-1914: Space, identity and power - Chircop, John; Chircop, John; Javier Martinez, Francisco (Manchester University Press, 2018)
Mediterranean quarantines investigates how quarantine, the centuries-old practice of collective defence against epidemics, experienced significant transformations from the eighteenth century in the Mediterranean Sea, its original birthplace. The new epidemics of cholera and the development of bacteriology and hygiene, European colonial expansion, the intensification of commercial interchanges, the technological revolution in maritime and land transportation and the modernisation policies in Islamic countries were among the main factors behind such transformations. The book focuses on case studies on the European and Islamic shores of the Mediterranean showing the multidimensional nature of quarantine, the intimate links that sanitary administrations and institutions had with the territorial organisation of states, international trade, the construction of national, colonial, religious and professional identities of political regimes.
Funded by: European Commission's OpenAIRE project
eng
Keywords: Quarantine -- Law and legislation -- Mediterranean Region -- History; Quarantine -- Political aspects -- Mediterranean Region -- History; Quarantine -- Mediterranean Region -- History; Quarantine -- history; c 1500 onwards to present day; European history; European history; History and Archaeology; History of medicine; History of medicine; History: earliest times to present day; History: specific events and topics; History: specific events and topics; History; History; Humanities; MEDICAL / History; MEDICAL -- Forensic Medicine; MEDICAL -- Preventive Medicine; MEDICAL -- Public Health; Medicine and Nursing; Medicine: general issues; Medicine: general issues; Medicine; Modern history to 20th century: c 1700 to c 1900.; Quarantine; Quarantine -- Law and legislation; Regional and national history; Social and cultural history; Social and cultural history; Society and social sciences Society and social sciences; Society and Social Sciences; Time period qualifiers; identity; long 19th century; mediterranean; power; quarantine; space